Caribbean Report 11-01-1995 - Crosskill, Hugh (anchor); Robotham, Paul (interviewee); Lukin, Vladimir (interviewee); Orr, Carol (correspondent); Halford, David (interviewee); Coughlan, Geraldine (correspondent); Kastov, Rene (interviewee); Ransome, Debbie (correspondent) (The British Broadcasting Corporation, 1995)
In this report, Jamaican and Guyanese students in Russia are warned to steer clear of war-torn Chechnya. Paul Robotham, Charge d'Affaires of the Jamaican Embassy in Moscow, assesses the situation and its impact on democracy in Russia. Carol Orr reports on Greenpeace, an international environmental lobby group and their vessel Rainbow Warrior as they began a six week tour in the Caribbean to oppose the shipment of nuclear wastes through the Caribbean Sea. In Auckland, New Zealand, West Indies cricket manager, David Halford answers questions on the availability of Richie Richardson and Carl Hooper for the New Zealand tour. Geraldine Coughlan reports on the pressure placed on BWIA to resume direct flights from St. Martin to Haiti by the Haitian community. Meanwhile as BWIA adapts to its new ownership and profit-oriented mandate, a new airline company, Air St. Maarten is filling the void left on this route. Debbie Ransome reports on the European Union banana regime and the US concerns that this regime harms its interests. The US is contemplating the possibility of retaliatory action over the regime and is now investigating Latin American producers who have opted out of the fight. This investigation will continue for the next year.
1. Headlines with Hugh Crosskill (00:00-00:34)
2. Report of the crisis in Chechnya (00:35-01:03)
3. Interview with Paul Robotham on the crisis and his advice to Jamaican and Guyanese students (01:04-02:34)
4. Interview with Vladimir Lukin on the crisis and how it is viewed in Russia (02:35-03:12)
Keywords: Chechnya (Russia) -- History -- Civil War, 1994; Russia (Federation) -- Relations -- Chechnya; West Indian students -- Jamaica; West Indian students -- Guyana; Foreign study; Hazardous wastes -- Caribbean Area; Radioactive waste disposal -- Caribbean Area; Hazardous wastes -- Transportation -- Caribbean Area; Cricket -- West Indies; Cricket players -- West Indies; Cricket -- Tournaments -- West Indies; Aeronautics -- Flights -- Management; Air travel -- Saint Martin; Air travel -- Haiti; Banana trade -- Latin America; Import quotas -- European Union countries; European Union countries -- Economic policy; United States -- Commerce -- European Union countries